Penggunaan Two-Tier Multiple Choice Diagnostik Test untuk mengidentifikasi Miskonsepsi Siswa Kelas X SMAN 1 Tangerang Selatan Pada Materi Larutan Elektrolit dan Non Elektrolit - Rizkyta Ananda, Lintang; Suharto, Hari (LPPM Universitas Negeri Jakarta, 2021)
This study aims to assess the level of student’s conceptual understanding and diagnose student’s misconception of electrolyte and non-electrolyte solutions. The measurement of misconceptions is using Two-Tier Multiple-Choice Diagnostic Test instrument with the Rasch model. This research was conducted on 189 students in class X SMAN 1 Tangerang Selatan and interviewed 40 students. The results is indicate that there are still misconceptions in electrolyte and non-electrolyte solution concept, as shown as 28% misconceptions in level 1; 33% in level 2; and 35% in level 3. Keywords Misconceptions, Electrolyte and Non-Electrolyte Solutions, Conceptual Understanding, Two-Tier Multiple-Choice Diagnostic Test.